THE MATTER OF PENSIONS IN THE LIGHT OF THE LEGISLATION, THE DECISIONS OF THE CONSTITUTIONAL COURT AND THE NEW SOCIAL REALITIES - Marta-Claudia CLIZA (Challenges of the Knowledge Society)
The public pension system has always raised many questions marks, firstly for its beneficiaries. Additionally, the Romanian legislation through which this system has been implemented has been objected against and the constitutional challenge has arrived on the bench of the Romanian Constitutional Court. This study wants to analyse the pension system starting from the economic background and ending with the legal one. In relation to the current system, the position of the Constitutional Court has been and is extremely clear, so that any legislative amendment, either at the initiative of the Parliament or at the initiative of the Government, by emergency ordinance, must take into account the constitutional requirements.